Allelopathic effect of Eucalyptus globulus and Pinus halepensis litter on high Andean wild plant species, Peru: Allelopathy in high Andean wild plants, Peru. - Panca-Jevera, Max Peter; Villanueva-Mamani, Dianet Christa; Gutierrez-Flores, Ivon Rocio (Ecosistemas y Recursos Agropecuarios, 2024)
Invasive alien plant species cause serious impacts on the structure and functioning of invaded ecosystems, leaving native species at a disadvantage. Eucalyptus globulus and Pinus halepensis are two species characterized by their wide distribution and high competitive ability. The objective of this study was to compare the allelopathic effect of E. globulus and P. halepensis litter leachate on germination, growth and species diversity of wild high Andean plants.  We collected 30 soil samples from the first 10 cm from 1 m2 quadrats. Leachate negatively affected germination, growth, and diversity of wild plant species, particularly eucalyptus leachate. As this is one of the few studies carried out in high Andean areas, it is necessary to carry out studies under natural conditions and on larger time scales, to more accurately assess the effects on biodiversity.
Keywords: Eucalyptus. Exotic plants. Litter leached. Pinus. Seed bank.